Breast cancer prevention information seeking behavior and interest on cell phone and text use: a cross-sectional study in Malaysia - Akhtari-Zavare, Mehrnoosh; Ghanbari-Baghestan, Abbas; Abd Latiff, Latiffah; Khaniki, Hadi (Asian Pacific Organization for Cancer Prevention, 2015)
Background: Breast cancer is the most common cancer and the second principal cause of cancer deaths among women worldwide, including Malaysia. This study focused on media choice and attempted to determine the communication channels mostly used and preferred by women in seeking information and knowledge about breast cancer. Materials and methods: A cross sectional study was carried out to examine the breast cancer prevention information seeking behavior among 450 students at one private university in Malaysia. Results: The mean age of respondents was 25±4.3 years. Common interpersonal information sources were doctors, friends, and nurses and common channel information sources were television, brochure, and internet. Overall, 89.9% used cell phones, 46.1% had an interest in receiving cell phone breast cancer prevention messages, 73.9% used text messaging, and 36.7% had an interest in receiving text breast cancer prevention messages. Bivariate analysis revealed significant differences among age, education, nationality and use of cell phones. Conclusions: Assessment of health information seeking behavior is important for community health educators to target populations for program development.